A Queen’s jewel box: the 1566 inventory of Mary Queen of Scot’s Jewels. - Alison Rosie (Royal Studies Journal, 2025)
In the summer of 1566, before the birth of her son James, later James VI and I, Mary Queen of Scots annotated an inventory of her jewels with bequests to her French and Scottish relatives, courtiers and servants. The inventory is often called her testamentary inventory as, while we know that Mary drew up a will on the 9th June and that two copies were made, none of the three has survived. The document gives us a precious insight into a luxurious collection of jewels worthy of a Renaissance Queen, and largely dispersed after her imprisonment in Lochleven and flight to England, as well as into Mary’s familial and political networks at that particular juncture. The article examines the types of jewels listed, what they say about the Renaissance mindset and culture, and looks at the individuals and groups who were at the forefront of her mind when she made her annotations.